The Effect of Investment Opportunity Set (IOS), Earnings Persistence and Accounting Conservatism on Earnings Quality with Voluntary Disclosure as an Intervening Variable - Dian Islamiati (Profesional Muda Cendekia Publishing, 2023)
The main problem of this research is earnings quality. Earnings quality is very important for investors and is the center of attention for users of financial statements, because it will help them reduce information risk. Investors will tend to calculate information risk by conducting analysis so that it does not contain a large risk of loss. Investors can know that there is a poor allocation of resources in companies with low earnings quality. The purpose of this study is to determine the effect of investment opportunity set, earnings persistence and accounting conservatism on earnings quality in food and beverage companies listed in ISSI in 2018-2021 with voluntary disclosure as an intervening variable. This research is classified as a quantitative research with a population of 25 food and beverage companies registered at ISSI. The research sample was determined by purposive method with certain criteria so that the sample used was 18 companies. so that 72 data were obtained from the sample in the 2018-2021 observation period. the type of data used is secondary data. to test the intervening variables used path analysis method. The research results show that the investment opportunity set, earnings persistence and accounting conservatism and voluntary disclosure have a negative effect on earnings quality. the variables ios and conservatism have a negative and significant effect on earnings quality, while the earnings persistence variable has a positive effect on quality. The results of this study also indicate that voluntary disclosure is only able to mediate accounting conservatism on earnings quality.